Financial innovation and its governance: Cases of two major innovations in the financial sector - Keren Naa Abeka Arthur (Financial Innovation, 2017)
Abstract The power of financial innovations to affect societies on global and intergenerational levels compels us to ask how we can ensure their responsible emergence in society. This requires an understanding of how innovation occurs and how it is governed in practice. Despite this, there is little research on the process and governance of financial innovation. The few studies conducted in this area have focused on the ‘backend’ of the innovation process. Therefore, using data from secondary sources, this study investigates how two major financial innovations occurred and were governed, and it discusses the findings in relation to those in the literature. This approach revealed that innovation processes fall within a continuum ranging from structured to unstructured. Moreover, lead times are potentially longer for innovations that are significantly disruptive, new to the market, and technological in nature. Finally, innovation processes can involve multiple stakeholders who use both statutory regulation and self-regulation for innovation governance. This paper concludes that innovation processes and their governance can vary significantly according to different areas of the financial landscape and associated innovation contexts. Thus, there is a need for more empirical work to understand such variability and practices in the sector as a whole.